Incisor ridge modification of the mandibles in freshwater crayfish, Astacus leptodactylus - Harlioglu, MM (Kluwer Academic Publ, 2000)
The differences in the ridge structure of the mandibles of different size Astacus leptodactylus (32-80 mm carapace length, CL) were investigated. The results showed that a modification occurs with an increase in size in the incisor ridge of mandibles in A. leptodactylus. The results also showed that A. leptodactylus possesses four different types of ridge structure in the mandibles. These are: (1) Incisor ridge with big teeth (dentate crenate), (2) Blade-like incisor ridge with numerous small teeth, (3) Blade-like ridge (toothless), (4) Blunt ridge. In conclusion, it is thought that the incisor ridge modification of the mandibles may cause the difference in the food choice of different size A. leptodactylus, because, crayfish possessing different ridge structures of the mandible may probably feed on different type of food.
Keywords: crayfish (Astacus leptodactylus); mandible; modification; ridge structure